2021
DOI: 10.1186/s43141-021-00118-1
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulated VEGF121-PLA microparticles promote angiogenesis in human endometrium stromal cells

Abstract: Background In this study, Vascular Endothelial Growth Factor 121 expressed abundantly in endometrial stromal cells is encapsulated with poly-l-lactide and characterized the properties for endometrial angiogenesis. We studied the migration, proliferation and the protein levels of human immortalized endometrium stromal cells after treating the cells with recombinant Vascular Endothelial Growth Factor (200 and 500 nanogram), and poly-l-lactide loaded Vascular Endothelial Growth Factor 121 (day 1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
2
0
1
Order By: Relevance
“…Specifically, hUC-PRP reduced endometrial fibrosis, increased endometrial area and gland density, and restored the functionality of the tissue by enhancing neovascularization, cell proliferation and activating regenerative molecular pathways (i.e. PI3K/Akt), which are involved in cell survival and decidualization ( Fabi et al , 2017 ) or re-epithelialization (by increasing VEGF gene expression) ( Abraham et al. , 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, hUC-PRP reduced endometrial fibrosis, increased endometrial area and gland density, and restored the functionality of the tissue by enhancing neovascularization, cell proliferation and activating regenerative molecular pathways (i.e. PI3K/Akt), which are involved in cell survival and decidualization ( Fabi et al , 2017 ) or re-epithelialization (by increasing VEGF gene expression) ( Abraham et al. , 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, scientists have shown that VEGF acts via the PI3K/AKT signaling pathway to promote EPC mobilization[ 43 ]. Differential gene expression analysis showed that high levels of PI3K and AKT increased VEGF expression and induced angiogenesis in EPCs[ 44 , 45 ]. The P38-MAPK pathway was also associated with the differentiation and mobilization EPCs from the bone marrow, which is the main source[ 46 , 47 ].…”
Section: Epcs and Coronary Artery Diseasementioning
confidence: 99%
“…Морфологический субстрат нарушения васкуляризации -склероз сосудов эндометрия и снижение экспрессии васкулоэндотелиального фактора роста (VEGF), максимум которого должен регистрироваться в средней секреторной фазе менструального цикла [7]. Важнейшую роль в развитии ХЭ играет трансформирующий фактор роста (TGF-β), который служит гистологическим маркером фиброза в тканях и показывает тяжесть заболевания [8,9].…”
unclassified